French Landscape Drawings and Sketches of the Eighteenth Century - Bacou, Roseline (London : British Museum Publications, 1977)
Patel, Pierre ; Silvestre, Israel ; Van Der Meulen, Adam Frans ; Desportes, François ; Gillot, Claude ; Watteau, Antoine ; Oudry, Jean-Baptiste ; Mariette, Pierre-Jean ; Portail, Jacques-André ; Silvestre, Nicolas-Charles ; Natoire, Charles-Joseph et al.
French Landscape Drawings and Sketches of the Eighteenth Century, Catalogue of a Loan Exhibition from the Louvre and other French Museums at the Department of Prints and Drawings in the British Museum, London, 1977
boek